2021
DOI: 10.3390/biom11111673
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Associated with Ribosomes in Human Adipose-Derived Stem Cells: From RNAs to Microproteins

Abstract: Ribosome profiling reveals the translational dynamics of mRNAs by capturing a ribosomal footprint snapshot. Growing evidence shows that several long non-coding RNAs (lncRNAs) contain small open reading frames (smORFs) that are translated into functional peptides. The difficulty in identifying bona-fide translated smORFs is a constant challenge in experimental and bioinformatics fields due to their unconventional characteristics. This motivated us to isolate human adipose-derived stem cells (hASC) from adipose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 86 publications
2
6
0
Order By: Relevance
“…Small open reading frame-encoded peptides (SEPs) are microproteins of less than 100–150 amino acids (AA), which are widely distributed in different species (yeast, Drosophila, mice, human, plants, etc.) and play crucial roles in transcriptional regulation, metabolism, cell growth and development, tumorigenesis, calcium transport, and stress response. , In prokaryotes, some SEPs of Escherichia coli were found to be differentially expressed under stress conditions (heat shock, oxidative stress, and acid stress) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small open reading frame-encoded peptides (SEPs) are microproteins of less than 100–150 amino acids (AA), which are widely distributed in different species (yeast, Drosophila, mice, human, plants, etc.) and play crucial roles in transcriptional regulation, metabolism, cell growth and development, tumorigenesis, calcium transport, and stress response. , In prokaryotes, some SEPs of Escherichia coli were found to be differentially expressed under stress conditions (heat shock, oxidative stress, and acid stress) .…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has shown that microproteins can play an essential role in the stress response of prokaryotes and eukaryotes. 4,5 Small open reading frame-encoded peptides (SEPs) are microproteins of less than 100−150 amino acids (AA), which are widely distributed in different species (yeast, 6 Drosophila, 7 mice, 8 human, 9 plants, 10 etc.) and play crucial roles in transcriptional regulation, metabolism, cell growth and development, tumorigenesis, calcium transport, and stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery, numerous sites of ribosome translation beyond the presently annotated CDS have been revealed [47] . Furthermore, long noncoding RNA’s role in translational regulation has also been elucidated [48] . Despite its advances in translatome study, there are also many challenges that this method may come with.…”
Section: Discussionmentioning
confidence: 99%
“…Ribo-seq is based on ribosome-protected RNA fragments (RPFs) after translation inhibition to map translation status. 55 …”
Section: Filtration Of Assembled Transcriptsmentioning
confidence: 99%